Desain Sistem Informasi Klaim BPJS Pasien Penyakit Dalam dengan Metode V Model - Sagita, Dina; Yunengsih, Yuyun; Abdussalaam, Falaah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Technology is currently very rapidly developing in all fields including the health sector, one of which is a hospital in a medical record agency, namely the claiming of BPJS internal medicine polyclinic patients who have not been computerized. The results of research conducted by the author found several problems, namely incomplete internal medicine polyclinic patient data, unfilled entry and exit dates, vacant diagnoses and anamnesis. So that it can affect the claiming of BPJS polyclinic internal medicine patient files, therefore, an information system is needed to support the completeness of BPJS patient medical record files so that claims are made quickly and accurately. Methods for collecting research data used include literature studies, interviews, and observations. The design of the information system uses the V model with the stages of Verification, Validation, Coding. System development consists of Flowmap, DFD, and ERD. then implemented using microsoft visual studio 2010 and database using microsoft access 2021. The results of designing an information system using the methods that have been chosen can help the performance of officers facilitate claiming and support the completeness of the medical record files of BPJS internal medicine polyclinic patients for accurate claiming.